Genetic analysis of a pedigree with MECP2 duplication syndrome in China - Lan Zeng; Hui Zhu; Jin Wang; Qiyan Wang; Ying Pang; Zemin Luo; Ai Chen; Shengfang Qin; Shuyao Zhu (BMC, 2024)
Abstract Background MECP2 duplication syndrome (MDS) is a rare X-linked genomic disorder that primarily affects males. It is characterized by delayed or absent speech development, severe motor and cognitive impairment, and recurrent respiratory infections. MDS is caused by the duplication of a chromosomal region located on chromosome Xq28, which contains the methyl CpG binding protein-2 (MECP2) gene. MECP2 functions as a transcriptional repressor or activator, regulating genes associated with nervous system development. The objective of this study is to provide a clinical description of MDS, including imaging changes observed from the fetal period to the neonatal period. Methods Conventional G-banding was employed to analyze the chromosome karyotypes of all pedigrees under investigation. Subsequently, whole exome sequencing (WES), advanced biological information analysis, and pedigree validation were conducted, which were further confirmed by copy number variation sequencing (CNV-seq). Results Chromosome karyotype analysis revealed that a male patient had a chromosome karyotype of 46,Y,dup(X)(q27.2q28). Whole-exon duplication in the MECP2 gene was revealed through WES results. CNV-seq validation confirmed the presence of Xq27.1q28 duplicates spanning 14.45 Mb, which was inherited from a mild phenotype mother. Neither the father nor the mother's younger brother carried this duplication. Conclusion In this study, we examined a male child in a family who exhibited developmental delay and recurrent respiratory tract infections as the main symptoms. We conducted thorough family investigations and genetic testing to determine the underlying causes of the disease. Our findings will aid in early diagnosis, genetic counseling for male patients in this family, as well as providing prenatal diagnosis and reproductive guidance for female carriers.